Occupational and non-occupational factors of post-COVID-19 condition: a cross-sectional survey in the French general working population - Joël Coste; Cyrille Delpierre; Tatjana T Makovski; Melissa Rushyizekera (BMJ Public Health)
Introduction Although the working population carries the greatest burden of long COVID, occupational and non-occupational factors of the condition have not yet been well documented in this population. The aim of this study was to investigate these factors.Methods A nationwide random sampling cross-sectional survey was conducted among the adult population in mainland France after the large Omicron waves in the autumn of 2022. Post-COVID-19 condition (PCC) was defined according to the WHO. Associations of occupational and non-occupational factors with PCC were tested in a conceptual model accounting for the relationships between these factors and considering two control groups (previously infected participants without PCC and participants with no reported or diagnosed SARS-CoV-2 infection). Interactions between occupational and non-occupational factors were considered.Results The survey included 1131 working adults. PCC was positively associated with reported infection while providing care (prevalence ratio (PR)=2.06 (95% CI 1.08 to 3.94)), being in contact with a colleague (PR=1.61 (95% CI 1.04 to 2.48)) and increased workload (PR=2.85 (95% CI 1.12 to 7.24)), whereas it was negatively associated with reported infection while being in contact with the public or clients (PR=0.23 (95% CI 0.07 to 0.76)). Several non-occupational factors were associated with PCC: sex, household size, household financial satisfaction, number of pre-existing chronic conditions, anxiety, injury sequelae and perceived SARS-CoV-2 infection severity. No interactions were found between these factors.Conclusions Reducing the burden of long COVID in the working population requires public health strategies that consider a wide spectrum of factors, including work conditions in a broad sense. Specific attention should be given to the most vulnerable workers accumulating such factors.